Genome Sequence of Pseudomonas citronellolis SJTE-3, an Estrogen- and Polycyclic Aromatic Hydrocarbon-Degrading Bacterium - Zheng, Daning (Genome Announc, 2016)
Pseudomonas citronellolis SJTE-3, isolated from the active sludge of a wastewater treatment plant in China, can utilize a series of environmental estrogens and estrogen-like toxicants. Here, we report its whole-genome sequence, containing one circular chromosome and one circular plasmid. Genes involved in estrogen biodegradation in this bacterium were predicted.